WOMEN AND CONTEMPORARY ART IN THE GULF identity, institutions and representation. - DeTurk, Sabrina ([S.l.] : ROUTLEDGE, 2022)
Women and Contemporary Art in the Gulf offers a unique focus on the roles of women in contemporary art, cultural production and arts institutions in the Gulf. Drawing on in-person experiences of the art and sites discussed, as well as research on regional artists and arts institutions, DeTurk argues that the Gulf Cooperation Council (GCC) countries of Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the United Arab Emirates have been largely excluded from the critical discourse about, and display of, contemporary Middle Eastern art. The book addresses this oversight by providing an examination of the work of several contemporary women artists from the Gulf region. DeTurk also discusses the role of women in museums and cultural institutions in the region, as well as the education systems available to emerging women artists. The discussion and analysis at the heart of the book connect to a range of larger themes, including the visual culture of patriarchy, connection to material culture and heritage, religious beliefs, trade and migration, rapid development, and the need to envision and create a post-oil economy. Women and Contemporary Art in the Gulf, with its examination of the critical role women play in the formation of the cultural landscape of the Gulf, is an important contribution to discourse around the changing role of the GCC. It will be essential reading for scholars and students engaged in the study of art history, visual culture, museums and heritage, and women and gender studies.
Keywords: Women and the arts -- Persian Gulf Region; Art, Modern -- 21st century; ART / General